2016
DOI: 10.18632/oncotarget.14116
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of tumor-initiating stem cells from mouse Krebs-2 carcinoma using a novel marker of poorly differentiated cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 107 publications
0
20
0
3
Order By: Relevance
“…Yet, several scenarios appear likely, for instance extracellular DNA may interfere with the processing of NER and homology repair DNA intermediates; alternatively, double-stranded DNA ends may exhaust the pool of repair machinery proteins or launch distinct repair cascades. Whichever the case may be, this interference leads to eradicate TISCs from the tumor site [ 1 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several scenarios appear likely, for instance extracellular DNA may interfere with the processing of NER and homology repair DNA intermediates; alternatively, double-stranded DNA ends may exhaust the pool of repair machinery proteins or launch distinct repair cascades. Whichever the case may be, this interference leads to eradicate TISCs from the tumor site [ 1 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-initiating stem cells (TISCs) were first described by Lapidot and Bonnet and Dick. 8 , 9 These cells are primarily responsible for tumor engraftment, and they provide high proliferative capacity of cancer cell population, contributing to the tumor structure 10 , 11 , 12 and metastasis. 13 15 Our recent studies have shown that eliminating such TISCs from the cancer cell population leads to tumor eradication and full recovery of tumor-engrafted mice (ascites and solid forms of murine Krebs-2 adenocarcinomas).…”
Section: Introductionmentioning
confidence: 99%
“…Ранее мы проанализировали 167 генов, демонстрирующих повышенную экспрессию в клетках асцитной карциномы Кребс2, проявляющих все свойства СРК [25] и на основании литературных данных определили 96 из них, являющихся потенциальными индукторами «плюрипотентного» фенотипа этих клеток [26]. В данной работе мы предприняли попытку проанализировать условия и механизмы активации экспрессии этих генов.…”
Section: Introductionunclassified